2023
DOI: 10.1042/bsr20222362
|View full text |Cite
|
Sign up to set email alerts
|

Acid–base imbalance as a risk factor for mortality among COVID-19 hospitalized patients

Abstract: Severe COVID-19 infection can lead to extensive lung infiltrate, a significant increase in the respiratory rate, and respiratory failure, which can affect the acid-base balance. No research in the Middle East has previously examined acid-base imbalance in COVID-19 patients. This study aimed to describe the acid-base imbalance in hospitalized COVID-19 patients, determine its causes, and assess its impact on mortality in a Jordanian hospital. The study divided patients into 11 groups based on arterial blood gas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
0
6
0
1
Order By: Relevance
“…A recent study by Jiang (2022) reveals 100% incidence of metabolic alkalosis in a cohort of critically ill patients with mortality rate of 81.3% compared to 50% incidence in patients with severe form of the disease and mortality rate of 21.4%. Al-Azzam et al (2023) also demonstrate a significant association of altered AB homeostasis with mortality rates among patients diagnosed with COVID-19, with significantly higher risks of lethal outcome in patients with metabolic acidosis associated with respiratory compensation, respiratory alkalosis with metabolic compensation and even patients with uncompensated respiratory acidosis. Mansouri et al (2022) observed AB imbalances in 87.7% of patients hospitalized with COVID-19, particularly respiratory alkalosis in 22.4% of the cases.…”
Section: Survey Methodologymentioning
confidence: 78%
“…A recent study by Jiang (2022) reveals 100% incidence of metabolic alkalosis in a cohort of critically ill patients with mortality rate of 81.3% compared to 50% incidence in patients with severe form of the disease and mortality rate of 21.4%. Al-Azzam et al (2023) also demonstrate a significant association of altered AB homeostasis with mortality rates among patients diagnosed with COVID-19, with significantly higher risks of lethal outcome in patients with metabolic acidosis associated with respiratory compensation, respiratory alkalosis with metabolic compensation and even patients with uncompensated respiratory acidosis. Mansouri et al (2022) observed AB imbalances in 87.7% of patients hospitalized with COVID-19, particularly respiratory alkalosis in 22.4% of the cases.…”
Section: Survey Methodologymentioning
confidence: 78%
“…However, over-compensation can lead to alkalosis, which is also seen in acute SARS-CoV-2 infections. 73% of patients with moderate-to-severe COVID-19 present with either acidosis or alkalosis (11), with acidosis or compensated respiratory alkalosis significantly increasing the risk of death (12). Similarly, acute disease outcomes were worse in patients with high or low blood bicarbonate levels (13) and in those with elevated LDH (14), suggesting that acidosis may play a role in the pathogenesis of acute COVID-19 (15).…”
Section: Inflammatory Acid-base Disruptions In Pascmentioning
confidence: 99%
“…Patients infected with SARS-CoV-2 may have different clinical presentations, from asymptomatic infection to severe respiratory failure requiring admission to the high-dependency unit or intensive care unit (ICU) and often leading to death [10]. The main reason for ICU admission of severe COVID-19 patients is severe respiratory failure; however, critically ill COVID-19 patients often present with metabolic abnormalities that seem to affect their outcome [11][12][13]. Among these metabolic abnormalities, metabolic acidosis seems to be related to a worse prognosis [12].…”
Section: Introductionmentioning
confidence: 99%
“…The main reason for ICU admission of severe COVID-19 patients is severe respiratory failure; however, critically ill COVID-19 patients often present with metabolic abnormalities that seem to affect their outcome [11][12][13]. Among these metabolic abnormalities, metabolic acidosis seems to be related to a worse prognosis [12].…”
Section: Introductionmentioning
confidence: 99%